Cocoa pod husk biochar amendment on potassium dynamics in a tropical acidic soil - Neenu, S.; Gopal, Murali; Gupta, Alka; Elain Apshara, S. (Journal of Plantation Crops, 2025)
Biochars are identified for use as an agricultural amendment worldwide. Cocoa Pod Husk (CPH), a waste from cocoa industry, was effectively converted into biochar having high nutrient value. The biochar thus produced was found to have high potassium content, a limiting nutrient in acidic soils. However, it was important to know the different fractions of potassium present in the biochar when used as an amendment in soil. Hence, an incubation experiment was conducted to study the K dynamics in soils amended with CPH biochar. For this, soils from coconut cultivated fields of CPCRI, Kasaragod were collected and amended with CPH biochar @ 0, 5, 10, 20 and 40 g kg-1. Mixture of soil and biochar and soil alone were kept at 60% field capacity under room temperature conditions for 30 days. Following incubation period, all samples were air-dried and analyzed for different potassium fractions. The results showed that with increasing biochar application rates, all potassium fractions, as well as total potassium, increased. However, when the percentage contribution of each fraction to total potassium was calculated, it became evident that water-extractable K, exchangeable K, and non-exchangeable K fractions exhibited an upward trend (6.8, 8.9, and 7 % respectively), while the lattice (fixed) potassium fraction declined (22.7 %). Since the availability of potassium is mainly determined by the water-extractable, exchangeable, and non-exchangeable fractions, the amendment of soil with cocoa pod husk biochar enhanced these fractions in the soil, thereby improving potassium availability. The present study clearly indicated that amendment of soil with CPH Biochar @ 5-10 g kg-1 was beneficial to improve the available status of potassium in a tropical acidic soil.